Utilização do POC-CCA como diagnóstico, taxa de cura e reinfecção na infecção por Schistosoma mansoni em escolares em área de moderada endemicidade no Brasil - Costa, Mikael Ferreira (2020)
The Schistosoma mansoni is the disease-causing parasites of schistosomiasis, tropical disease neglected with great impact on morbidity and mortality in underdeveloped countries. The diagnosis method Kato-Katz is considered a benchmark test, however it has low sensitivity. Therefore, aiming to improve the disease diagnosis, the Point-of-care (POC) quick test that identifies circulating cathodic antigen (CCA) has been used as new form of identifying the disease. The POC-CCA comes with the proposal of being a method that consists of a quick mapping of positive cases, which can also be used to monitor the cure control and to reevaluate the reinfection of individuals, especially in endemic areas. Goal: To evaluate the prevalence of schistosomiasis in schoolchildren with POC-CCA as a diagnostic method and of tracking cure control in schoolchildren undergoing antiparasitic treatment. Methodology: Longitudinal epidemiological study, carried out with school-aged individuals (6-22 years old), in the municipality of Malhador/Sergipe in 5 endemic communities to schistosomiasis. The schoolchildren were diagnosed using the POC-CCA urine test, after the identification of the positives it was carried out the treatment with 133 pounds of Praziquantel. After 30 days of treatment it was made the collection of urine samples of treated individuals for the cure evaluation. Then, a year after treatment it was carried out the tracking to verify the reinfection rate of individuals who underwent the first treatment. Results: Were collected samples of 555 schoolchildren, 52% male and 48% female. Considering the trace as negative result, 112/555 (20,2%) had a positive diagnosis. However, if considering the trace as positive, increases the number of infected to 186/555 (33,5%) positive cases, this difference is shown to have p <0.001. Every individual with positive band in the diagnosis and treated (162) did the cure control 30 days after treatment 33/162 (t+) (20,4%) individuals kept positive in the exam by quick test. One year after treatment were tracked 129 schoolchildren, among which 43 (33,3%) were negative. CONCLUSION: The POC-CCA test shows to be a good diagnostic method of the infection by S. mansoni, also showing to be useful for quick epidemiological mapping, cure control and verification of the rate of reinfection.